Threatened cetaceans in a potential deep seabed mining region, Clarion Clipperton Zone, Eastern Pacific, August 2023 - Young, Kirsten F.; Webber, Thomas; Karantzas, Leonidas; Miteva, Severina; Oakes, Grant; Santillo, David; Johnston, Paul (Frontiers in Marine Science, 2025)
The Clarion Clipperton Zone (CCZ) of the Eastern Pacific is an 6 million km2 abyssal area punctuated by seamounts. The CCZ is a focus for potential mining, although this is not, as yet, a commercial reality. Records from online repositories and field guides suggest that up to 30 cetacean species are present in the CCZ, though dedicated surveys have yet to be published. We report the results of a passive acoustic survey for cetaceans conducted over 13 days during summer 2023 in two blocks of the CCZ earmarked for deep seabed mining – NORI-d and TOML-e. The areas surveyed had a mean depth of 4259 m, with no charted seamounts, with 4,328 km of survey effort (273 hours of continuous recordings). In total, there were 74 acoustic detections, with six visual encounters. We report the presence of a sperm whale (Physeter macrocephalus) (one individual), Risso’s dolphins (Grampus griseus) (two groups) and common dolphins (Delphinus delphis) (one group, confirmed by visual sighting). We also acoustically encountered 70 dolphin groups that could not be identified to species level. No baleen whales, kogiids or beaked whales were detected during this short survey. Beaked whales are challenging to detect, such that a lack of detections cannot be taken to confirm the absence of such species. We confirm one threatened species present in these blocks of the CCZ – sperm whales – and suggest that more extensive data are urgently needed to understand the risk of harm to cetaceans that may arise from human activities, including deep-sea mining.